Pengaruh Electronic Word Of Mouth dan Digital Payment terhadap Purchase Intention pada Aplikasi E-Commerce - Meytra Taufik, Henry; Pratama, Aldrik Rifky (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
As a result of the evolution of information and technology, many corporate sectors are currently using technology and media as instruments in marketing efforts. The evolution of advertising has emerged as a modern trend for achieving long-term economic success. However, when a business chooses the wrong social media platform, problems arise that have a negative impact on the business. This study aims to find out how the e-commerce company Tokopedia in the city of Bandung uses electronic word of mouth and digital payments for easy payment. 120 participants were randomly selected to participate in this study and utilized smartphone applications for internet shopping. This study uses a multiple linear regression analysis strategy using SPSS software version 26. The results show that electronic word of mouth and digital payment variables have an effect on purchase intention and can be categorized as good.